Severe pediatric adenovirus 7 disease in Singapore linked to recent outbreaks across Asia - Ng, Oon-Tek (2015)
During November 2012–July 2013, a marked increase of adenovirus type 7 (Ad7) infections associated with severe disease was documented among pediatric patients in Singapore. Phylogenetic analysis revealed close genetic links with severe Ad7 outbreaks in China, Taiwan, and other parts of Asia.